Produção de Conhecimento em um ecossistema de inovação: o caso do Estado de Minas Gerais - Leticia de Castro Peixoto (2020)
The present research project investigated the effects of actions taken by the government, industry and academic sectors aimed at Knowledge production in the Brazilian state of Minas Gerais State. Such actions included: direct financial investments, human capital development, patents generation, initiatives to connect with the technological ecosystem, among others that have previously been made publicly available. The data upon which this study is based comes from the InovaData platform, which encompasses data from more than 500 technology-based companies in Minas Gerais as well as open data released on Government platforms between 2000 and 2017. The Triple Helix model lens was applied, whereby the innovation potential in a knowledge-based economy lies on the hybridization of industry, academia and Government for the generation of new forms of production, transference and application of knowledge. The empirical model proposed outlined a function for the knowledge production for Minas Gerais state (MG). The model results pointed to a stronger university contribution to MG scenario and some mesoregions particularities were explored. Therefore, the study confirms the hypotheses that postgrad students, patents and publications are positive related to innovation in this region.